Current State and Problems of the Border Regions of Russia with Belarus - Alexander P. Katrovsky; Valentin S. Korneevets (International Journal of Economics and Financial Issues, 2015)
The article describes the characteristics and problems of socio-economic development of the Russian border regions with Belarus. The basic stages of development and transformation of the economic and resettlement structures are revealed. Particular attention is paid to the strengthening peripheral effects in the development of the borderland in the post-Soviet era. It is noted that the economic stagnation and deindustrialization in the last decade is combined with the social degradation of the countryside and de-agrariation of the territory. Particular attention is given to the Smolensk oblast as a key link of the Russian-Belarusian borderland. The ways and directions of further development of the regions are presented. Paper argues on the need to develop a single concept and development programs of the Russian-Belarusian border area. The creation of the priority development areas in each of the border regions of Russia and Belarus proposed as an instrument of economic revitalization.